TA’LIQ TALAK PERSPEKTIF IMAM SYAFI'I DAN IMAM IBN HAZM - Huda, Afiful; Dyah Ayu Wardana, Febryani (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2020)
In marriage, an agreement can be made to avoid things that may not be desirable. In terms of marriage agreements, Imam Syafi'I and Imam Ibn Hazm have different opinions about the law. This study uses a qualitative literature approach. The result of this research is that there is a similarity in opinion between Imam Syafii and Imam Ibn Hazm in terms of the understanding of the marriage agreement. Then regarding the law, he both had different opinions, namely: Imam Shafi'i allowed and legalized the fall of divorce when the conditions had been fulfilled, while Imam Ibn Hazm had an invalid opinion, the divorce imposed outside the provisions of syara 'according to him was invalid because it violated the provisions Allah SWT. Then in terms of the legal basis used between Imam Syafii and Ibn Hazm is also different, namely: Imam Syafi'I uses al-Qur'an surah al-Maidah verse 5, the Hadith narrated by Imam Bukhari, as well as Hadith from Ibn Majah. Meanwhile, Imam Ibn Hazm used al-Qur'an surah at-Talaq verse 1 and hadith from Imam Abu Dawud.